ISOLATION AND STRUCTURE DETERMINATION OF ANTICANCER SUBSTANCES FROM MARINE MICROORGANISMS: A PRELIMINARY STUDY OF NEW BUTENOLIDE AS NEW ANTICANCER - Hatmandi, Ariani; Kanoh, Kaneo (Marine Research in Indonesia, 2008)
An investigation to find new anticancer substances from marine microorganisms was conducted at the Marine Biotechnology Institute, Kamaishi Campus, Iwate, Japan. The samples were from MBI microorganism collection. They were bacteria, actinomycetes and fungus. Mammalian cancer cells, A549, were used as screening medium. The method for screening of the targeted microorganism was micro plate method. HK294 was found as microorganism which has the most interesting phenomenon in inhibiting A549 cancer cells. HK294 was identified to be Streptomyces viridocyaneus (homology 99%) by its 16S rDNA sequence. The HK294 was cultured in Marine Broth medium and incubated at 30Â°C for seven days in 100 rpm orbital shaker incubator, to produce active substance. Silica Gel Column Chromatography and High Pressure Liquid Chromatography were used for separation of the active substances. NMR and Mass Spectrum were used for determination of the active substances. Butenolide, Teleocidin A1 and New Butenolide were isolated from this experiment. The New Butenolide is promising to be used for anticancer drug but it need further research.